2011
DOI: 10.1111/j.1365-313x.2011.04710.x
|View full text |Cite
|
Sign up to set email alerts
|

A cellular expression map of the Arabidopsis AUXIN RESPONSE FACTOR gene family

Abstract: SUMMARYThe plant hormone auxin triggers a wide range of developmental and growth responses throughout a plant's life. Most well-known auxin responses involve changes in gene expression that are mediated by a short pathway involving an auxin-receptor/ubiquitin-ligase, DNA-binding auxin response factor (ARF) transcription factors and their interacting auxin/indole-3-acetic acid (Aux/IAA) transcriptional inhibitors. Auxin promotes the degradation of Aux/IAA proteins through the auxin receptor and hence releases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
237
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(249 citation statements)
references
References 48 publications
(131 reference statements)
9
237
2
1
Order By: Relevance
“…In addition to identifying MP-dependent genes that are activated in vascular tissue, the embryonic root meristem or the root cap precursors, this analysis surprisingly also led to the identification of a set of auxin-dependent genes that mark the first ground tissue cells. Despite many efforts in dissecting the gene regulatory network that controls ground tissue development (5)(6)(7)(8)(35)(36)(37)(38)(39)(40)(41)(42), so far no factors have been identified that regulate ground tissue establishment. We now identify auxin response, and its effector MP, as regulators of this critical first step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to identifying MP-dependent genes that are activated in vascular tissue, the embryonic root meristem or the root cap precursors, this analysis surprisingly also led to the identification of a set of auxin-dependent genes that mark the first ground tissue cells. Despite many efforts in dissecting the gene regulatory network that controls ground tissue development (5)(6)(7)(8)(35)(36)(37)(38)(39)(40)(41)(42), so far no factors have been identified that regulate ground tissue establishment. We now identify auxin response, and its effector MP, as regulators of this critical first step.…”
Section: Discussionmentioning
confidence: 99%
“…The bdl inhibitor can inhibit ARFs other than MP (39), and it is therefore possible that differential gene expression upon local bdl expression is caused by inhibition of other ARFs, coexpressed with MP (40). To test whether these genes represent MP output, we analyzed the expression of these genes in mp mutant embryos.…”
Section: Mp Transcriptionally Controls the Regulatory Network For Groundmentioning
confidence: 99%
“…Our work ex situ has demonstrated the baseline for auxin response at the molecular level, which can now be used as a breadboard for testing additional layers of regulation and integration with other signaling pathways. In addition, a wealth of transcriptome data (42,43) can now be used to generate hypotheses about the likelihood of binding by a specific ARF through integration of cell type-specific expression maps of auxin signaling components (44) and binding-site preferences from protein binding arrays (16). Yeast auxin response circuits provide a resource to rapidly test these hypotheses and inform experimental designs in planta.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome encodes 29 Aux/IAA and 23 ARF factors. Genetics studies have shown that these factors may have both unique and redundant functions on plant growth and development, which likely depend on the specific patterns of expression of these factors on tissues or cells (6). The previous work on auxin signaling has focused mainly on development, and little is known about the specific role of the auxin receptors, ARF, and Aux/IAA proteins on plant responses to environmental cues.…”
mentioning
confidence: 99%